Compact ammonia/water absorption chiller of different cycle configurations: parametric analysis based on heat transfer performance - Tao, Xuan; Thanganadar, Dhinesh; Patchigolla, Kumar (MDPI, 2022)
Ammonia/water absorption chillers are driven by low-grade heat and cover wide refrigeration temperatures. This paper analyses single-stage ammonia/water absorption chillers. A numerical model was developed based on the heat exchanger performance. The model captures variational heat exchanger performances and describes the actual cycle with varying boundary conditions. The detrimental effects of refrigerant impurity were analysed quantitatively under different operating conditions. The model was validated with experimental data. A basic cycle and three advanced cycles were analysed for sub-zero refrigeration by comparing the thermodynamic performances. A compression-assisted cycle extended the activation temperature from 80 to 60 °C. At the heat source of 120 °C, when a counter-current desorber or bypassed rich solution was used, the COP increased from 0.51 to 0.58 or 0.57, respectively. The operating parameters included the heat source temperatures, heat sink temperatures, the mass flow rates and mass concentrations of rich solutions. Higher heat source temperatures increase cooling capacity. The increase was around 20 kW for the basic cycle of sub-zero refrigeration. There is an optimum heat source temperature maximising the COP. Higher heat source temperatures increased the refrigerant mass flow rate and reduced the mass concentration. The mass concentration can decrease from 0.999 to 0.960.
Keywords: ammonia/water; cycle configurations; temperature glide; heat source temperature; heat transfer model; plate heat exchanger; absorption cooling; solar refrigeration